Intravenous immunoglobulins and rituximab therapy for severe transplant glomerulopathy in chronic antibody‐mediated rejection: a pilot study. (30th March 2015) - Bachelet, Thomas; Nodimar, Celine; Taupin, Jean‐Luc; Lepreux, Sebastien; Moreau, Karine; Morel, Delphine; Guidicelli, Gwendaline; Couzi, Lionel; Merville, Pierre
Abstract Outcome of patients with transplant glomerulopathy (TG) is poor. Using B‐cell targeting molecules represent a rational strategy to treat TG during chronic antibody‐mediated rejection. In this pilot study, 21 patients with this diagnosis received four doses of intravenous immunoglobulins and two doses of rituximab (IVIG/RTX group). They were retrospectively compared with a untreated control group of 10 patients. At 24 months post‐biopsy, graft survival was similar and poor between the treated and the untreated group, 47% vs. 40%, respectively, p = 0.69. This absence of response of IVIG/RTX treatment was observed, regardless the phenotype of TG. Baseline estimated glomerular filtration rate (eGFR) and decline in eGFR during the first six months after the treatment were risk factors associated with 24‐month graft survival. The IVIG/RTX therapy had a modest effect on the kinetics of donor‐specific alloantibodies at M24, compared to the untreated group, not associated with an improvement in graft survival. The mean number of adverse events per patient was higher in the IVIG/RTX group than in the control group (p = 0.03). Taken together, IVIG/RTX treatment for severe TG during chronic antibody‐mediated rejection does not seem to change the natural history of TG and is associated with a high incidence of adverse events.